Illustration mitLastwagen viele Abgase entsendent, die einen Passanten umhüllen; um ca. 1950
Umwelt;Umweltschädigung;Schadensfaktor;Schadstoff;luftverunreinigender Stoff;Abgas Verkehr;Landverkehr;Strassenverkehr;Motorfahrzeug;Nutzfahrzeug